Adsorption and reaction mechanisms of direct palladium synthesis by ALD using Pd(hfac)₂ and ozone on Si (100) surface - Cheng, Chunyu (2022)
Palladium nanoparticles made by atomic layer deposition (ALD) normally involve formaldehyde or H2 as a reducing agent. Since formaldehyde is toxic and H2 is explosive, it is advantageous to remove this reducing step during the fabrication of palladium metal by ALD. In this work we have successfully used Pd(hfac)2 and ozone directly to prepare palladium nanoparticles, without the use of reducing or annealing agents. Density functional theory (DFT) was employed to explore the reaction mechanisms of palladium metal formation in this process. DFT results show that Pd(hfac)2 dissociatively chemisorbed to form Pd(hfac)* and hfac* on the Si (100) surface. Subsequently, an O atom of the ozone could cleave the C–C bond of Pd(hfac)* to form Pd* with a low activation barrier of 0.46 eV. An O atom of the ozone could also be inserted into the hfac* to form Pd(hfac-O)* with a lower activation barrier of 0.29 eV. With more ozone, the C–C bond of Pd(hfac-O)* could be broken to produce Pd* with an activation barrier of 0.42 eV. The ozone could also chemisorb on the Pd atom of Pd(hfac-O)* to form O3-Pd(hfac-O)*, which could separate into O-Pd(hfac-O)* with a high activation barrier of 0.83 eV. Besides, the activation barrier was 0.64 eV for Pd* that was directly oxidized to PdOx by ozone. Based on activation barriers from DFT calculations, it was possible to prepare palladium without reducing steps when ALD conditions were carefully controlled, especially the ozone parameters, as shown by our experimental results. The mechanisms of this approach could be used to prepare other noble metals by ALD without reducing/annealing agents.